Higher Order Continuum Modelling for Predicting the Mechanical Behaviour of Solid Foams. Issue 1 (December 2014) - Liebenstein, Stefan; Sandfeld, Stefan; Zaiser, Michael
Abstract A higher order continuum model is presented, which is able to capture size effects and regularize softening in rotational, shearing and especially compressive settings. It is shown that with a minimal setting of 3 additional constitutive parameters the model has all desired properties. For parameter identification an example system of a honeycomb structure is investigated. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)